Analisis Desain Pembelajaran STEM berdasarkan Kemampuan 4C di SD - Irman Artobatama; Ghullam Hamdu; Rosarina Giyartini (Indonesian Journal of Primary Education, 2020)
Abstract        Learning design in some elementary schools still uses learning methods that lack meaningful learning and lack of direct student involvement in each learning process so that the competencies possessed are less developed and do not yet involve engineering processes, technology in them. The less meaningful learning design has not been able to meet the demands of the 4C abilities (Creativity, Collaboration, Communication, and Critical thinking). This research was conducted to produce a learning design product STEM (Science, Technology, Engineering, and Mathematics) in elementary schools based on the ability of 4C. Qualitative research methods are used with data from FGD (Focus Group Discuss) results. Data collected by in-depth interviews and observations. The results showed that the learning design was based on 4C capabilities that had been developed valid and could be used. The validation process is carried out with expert judgment, and the use of the FGD results. The teacher's response to the FGD stated that it was good, easy to understand and could be used in elementary schools. This STEM learning design can be used as an alternative by the teacher in conducting the learning process that involves engineering and technology processes so that it can meet the demands of 4C capabilities.Abstrak        Desain pembelajaran di beberapa sekolah dasar masih menggunakan metode pembelajaran yang kurang memberikan kebermaknaan dalam pembelajaran dan kurangnya keterlibatan siswa secara langsung dalam setiap proses pembelajaran sehingga kompetensi yang dimiliki kurang berkembang serta belum melibatkan proses rekayasa, teknologi di dalamnya. Desain Pembelajaran yang kurang bermakna tersebut belum dapat memenuhi tuntutan kemampuan 4C (Creativity, Collaboration, Communication, and Critical thinking). Penelitian ini dilakukan untuk menghasilkan suatu produk desain pembelajaran STEM (Science, Technology, Engineering, and Mathematics) di sekolah dasar berdasarkan kemampuan 4C. Metode penelitian kualitatif digunakan dengan data dari hasil FGD (Focus Group Discuss). Data dikumpulkan dengan wawancara secara mendalam dan observasi. Hasil penelitian menunjukan bahwa desain pembelajaran berdasarkan kemampuan 4C yang telah dikembangkan secara valid dan dapat digunakan. Proses validasi dilakukan dengan petimbangan ahli, dan keterpakaian dari hasil FGD. Respon guru pada FGD  menyatakan sudah baik, mudah dipahami dan dapat digunakan di Sekolah Dasar. Desain pembelajaran STEM ini dapat dijadikan alternatif oleh guru dalam melakukan proses pembelajaran yang melibatkan proses rekayasa serta teknologi sehingga dapat memenuhi tuntutan kemampuan 4C.